Contribuição da biblioteconomia para a visibilidade das incubadoras de empresas brasileiras - Lorevice, Natália Cristina (Universidade Federal de São Carlos, 2023)
Brazilian business incubators are organizations that provide logistical, technical and managerial support to entrepreneurs with the aim of facilitating the creation of companies that carry out activities focused on innovation. The website Mapa Associados of the Associação Nacional de Entidades Promotoras de Empreendimentos Inovadores (Anprotec) provides data on different innovation environments, including incubators. However, some limitations were observed in the presentation of data on this portal: to view data from innovation environments, the system offers the user only four filters: environment, region, state and city. When applying the filters and selecting one of the listed incubators, the system displays a dialog box with the name of the incubator, its e-mail and its website. Therefore, there is absence of data that may be of interest to users, such as the type of incubators, the year of its creation, the managing entity. The system also does not allow browsing through available information or searching by area of expertise, for example. Given this fact, the study proposed to discuss the following research question: what is the contribution that Librarianship can make to increase the visibility of Brazilian business incubators? and it had as a main objective, to identify contributions from Librarianship to the visibility of Brazilian business incubators. The research is of applied nature, with qualitative approach, exploratory objectives and bibliographic procedures, with the adoption of the literature mapping method, and documentary procedures, with consultation on the incubators' websites. The social role of business incubators and the role of metadata in information architecture and information findability were discussed based on bibliographical research. The study also resulted in a proposal for guidelines for cataloging Brazilian business incubators, based on the comparison between the data obtained from consulting the incubators' websites and the description elements prescribed by the MARC 21 Community Information. As a conclusion, it was found that the application of these guidelines in an informational environment could expand the possibilities for searching and retrieving information about incubators, improving the presentation of results and increasing their visibility.
Librarianship's contribution to the visibility of Brazilian business incubators
Keywords: Incubadora de empresas; Metadados; Arquitetura da informação; Encontrabilidade da informação; Visibilidade; Business incubators; Metadata; Information architecture; Findability; Visibility; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::TECNICAS DE RECUPERACAO DE INFORMACAO